Combining methylated SDC2 test in stool DNA, fecal immunochemical test, and tumor markers improves early detection of colorectal neoplasms - Zeng, Tao; Huang, Zhongchao; Yu, Xufa; Zheng, Li; Liu, Tao; Tian, Boyu; Xiao, Siyu; Huang, Jiahui (Frontiers in Oncology, 2023)
Objective: To explore the value of testing methylated SDC2 (SDC2) in stool DNA combined with fecal immunochemical test (FIT) and serum tumor markers (TM) for the early detection of colorectal neoplasms.Methods: A total of 533 patients, including 150 with CRC (67 with early-stage CRC), 23 with APL, 85 with non-advanced adenomas and general polyps, and 275 with benign lesions and healthy controls. SDC2 was detected by methylation-specific PCR, FIT (hemoglobin, Hb and transferrin, TF) was detected by immunoassay, and the relationships between SDC2, FIT, and clinicopathological features were analyzed. Pathological biopsy or colonoscopy were used as gold standards for diagnosis, and the diagnostic efficacy of SDC2 combined with FIT and TM in CRC and APL evaluated using receiver operating characteristic (ROC) curves. This is a provisional file, not the final typeset article Results: SDC2 positive rates in early-stage CRC and APL were 77.6% (38/49) and 41.2% (7/17), respectively, and combination of SDC2 with FIT increased the positive rates to 98.0% (48/49) and 82.4% (14/17). The positive rates of SDC2 combined with FIT assay in the APL and CRC groups at stages 0-IV were 82.4% (14/17), 85.7% (6/7), 100% (16/16), 100% (26/26), 97.4% (38/39), and 100% (22/22), respectively. Compared to the controls, both the CRC and APL groups showed significantly higher positive detection rates of fecal SDC2 and FIT (χ2 = 114.116, P < 0.0001 and χ2 = 85.409, P < 0.0001, respectively). Our results demonstrate a significant difference in the qualitative methods of SDC2 and FIT for the detection of colorectal neoplasms (McNemar test, P < 0.0001).ROC curve analysis revealed that the sensitivities of SDC2 and FIT, alone or in combination, for the detection of early CRC and APL were 69.9%, 86.3%, and 93.9%, respectively (all P<0.0001). When combined with CEA, the sensitivity increased to 97.3% (P<0.0001).Conclusions: SDC2 facilitates colorectal neoplasms screening, and when combined with FIT, it enhances detection. Furthermore, the combination of SDC2 with FIT and CEA maximizes overall colorectal neoplasm detection.